Integrasi Kearifan Lokal dalam Mendorong Literasi Keuangan dan Kemandirian Siswa Berdaya Saing pada Madrasah Tsanawiyah (MTs) Lombok Timur - Ihsan; Baiq Salkiah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This study aims to analyze the integration of local wisdom as a strategic approach to improving financial literacy and independence among students at Islamic Junior High Schools (MTs) in East Lombok. Amidst the challenges of low national financial literacy, local wisdoms such as mutual cooperation (gotong royong), begawe (joint work), begibung (joint work), family social gatherings (arisan keluarga), and traditional crafts hold significant potential as contextual and accessible learning resources for students. This study employed descriptive qualitative methods through literature review, contextual observation, and thematic analysis to explore cultural values ​​relevant to financial learning. The results indicate that integrating local wisdom into learning improves students' understanding of money management, financial planning, risk management, and entrepreneurial skills through hands-on, experiential activities. Furthermore, this approach contributes to the development of financial character traits such as discipline, honesty, responsibility, and cooperation. However, its implementation still faces challenges such as a lack of culture-based modules, limited supporting facilities, and inadequate teacher training. This study recommends strengthening collaboration between madrasas, local governments, and the community to develop a sustainable, locally based financial literacy model.